Understanding the Impact of the COVID-19 Pandemic, Lockdowns and Social Isolation on Sleep Quality - O'Regan D (Dove Medical Press, 2021)
David O’Regan,1,2 Melinda L Jackson,3 Allan H Young,4 Ivana Rosenzweig1,5 1Sleep Disorders Centre, Guy’s and St Thomas’ Hospital, GSTT NHS, London, UK; 2Faculty of Life and Sciences Medicine, King’s College London, London, UK; 3Turner Institute for Brain and Mental Health, Monash University, Melbourne, Australia; 4School of Academic Psychiatry, IoPPN, King’s College London, London, UK; 5Sleep and Brain Plasticity Centre, CNS, IoPPN, King’s College London, London, UKCorrespondence: Ivana RosenzweigSleep and Brain Plasticity Centre, Department of Neuroimaging, Institute of Psychiatry, Psychology and Neuroscience, Box 089, De Crespigny Park, London, SE5 8AF, UKEmail ivana.1.rosenzweig@kcl.ac.ukAbstract: The uncertain, ever-changing and an ongoing nature of the COVID-19 pandemic means that it may take some time before we can fully appreciate the negative effect of the pandemic and lockdown on our sleep and mental health. It is increasingly recognised that in the aftermath of pandemic, several persistent sleep, neuropsychiatric and physical sequelae may continue long after the pandemic is over. A body of evidence to date also highlights a significant disparity in sleep and mental health difficulties in specific vulnerable groups in the community, with different temporal profiles and sleep issues that are reported. In this perspective, we argue for a possible mechanistic impact of the COVID-19 pandemic, with its imposed restrictions and social isolation on sleep quality. We similarly discuss some of the potential international differences, as well as similarities, behind reported idiosyncratic biological vulnerabilities that may have contributed to the genesis of sleep issues. Lastly, we propose some possible implementations and innovations that may be needed in restructuring of sleep disorders services in order to benefit recovering COVID-19 patients.Keywords: sleep, insomnia, hypersomnia, lockdown, COVID-19 pandemic, social isolation